Decreased neutrophil levels in bronchopulmonary dysplasia infants - Xingchao Li; Qian Wang; Ting Luo; Tao Li (Pediatrics and Neonatology)
Background: Previous studies have indicated that inflammation plays an important role in the occurrence and development of bronchopulmonary dysplasia (BPD); however, there were rare researches about the changes of neutrophils and their influence on the prognosis of BPD. Hence, we aimed to explore the changes in the number of peripheral blood neutrophils (PBNs), and the relationship between these changes and susceptibility to pulmonary infection among children with BPD. Methods: Firstly, the gene expression of lung tissues and the number of PBNs were respectively detected by RNA sequencing and complete blood count in the 85% O2-induced BPD model rats. Then it was analyzed the number of PBNs after birth and the incidence of pneumonia within 6 months of corrected age (CA) after discharge among full-term infants (FTIs: gestational age [GA] between 370/7 and 416/7 weeks, n = 88), preterm infants with (PTIs-BPD: GA <32 weeks, n = 35) or without BPD (PTIs-nBPD: GA <32 weeks, n = 41). Results: The levels of S100A8 and S100A9 mRNAs were significantly decreased in the lungs of BPD rats. Moreover, the number of PBNs was also decreased in BPD rats. The number of PBNs at birth in FTIs was significantly greater than that in PTIs-BPD or in PTIs-nBPD (p < 0.001), while those between PTIs-BPD and PTIs-nBPD showed no significant difference (p > 0.05). Although the peripheral blood neutrophils decreased overall after birth in both PTIs-nBPD and PTIs-BPD groups, only the reduction in the PTIs-BPD group was significant (p < 0.001). Importantly, at 36–37 weeks of postmenstrual age (PMA), the number of PBNs in PTIs-BPD was significantly fewer than that in PTIs-nBPD (p < 0.001). In addition, PTIs-BPD had a significantly higher incidence of pneumonia than PTIs-nBPD within 6 months of CA after discharge (p < 0.01). Conclusion: The number of PBNs in PTIs-BPD decreased progressively when compared to that in PTIs-nBPD, which might contribute to their susceptibility to pulmonary infection.